ANALISIS STRATEGI MARKETING TERHADAP MINAT KONSUMEN DALAM PENGGUNAAN JASA KEUANGAN POSPAY PADA PT POS INDONESIA (PERSERO) REGIONAL I SUMATERA - Dewi, Mutia Sari; Aslami, Nuri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
In determining the marketing strategy, we must be able to determine which consumers we can serve and meet their needs well and the company's way to convey their value to these consumers. This study aims to find out what marketing strategies are carried out by PT Pos Indonesia (Persero) Regional I Sumatra on consumer interest in using Pospay financial services. This research model uses an approach with observation and interview methods and involves 2 people. The results of this study are by providing information about products to the public, promotional activities through events, and also sponsorships, encouraging people to use pospay by introducing pospay services, the convenience provided by PT. Pos Indonesia to the public to use Pospay services, optimizing efforts in expanding the marketing target of Pospay products as well as another service of PT Pos Indonesia.